Efficiency of enhanced oil recovery’s and oil production stimulation’s methods at the oil fields of Khanty-Mansi Autonomous Okrug – Yugra - S. G. Kuzmenkov; M. I. Korolev; M. V. Novikov; A. N. Palyanitsina; O. A. Nanishvili; V. I. Isaev (Georesursy, 2024)
Stabilization of oil production at the level of 215–220 million tons/year, as well as its subsequent growth, is a priority task for the enterprises of the fuel and energy complex of Khanty-Mansi Autonomous Okrug – Yugra (KhMAO – Yugra). It is impossible to achieve this without the active implementation of the most effective modern technologies for enhanced oil recovery. This article aims to analyze the methods of enhanced oil recovery and and oil production stimulation methods (EOR and PS) used at the KhMAO – Yugra fields on an industrial scale, their features and their contribution to additional oil production from 2001 to 2021.The article describes such technologies as sidetracking (STB), physical and chemical methods (FCM), hydraulic fracturing (HF), bottom-hole treatment (BHT), hydrodynamic methods (HDM), horizontal well drilling (SHD), as well as other geological and technical measures (GTM) aimed at optimizing well operation (other methods (OM)). The study showed that FCM, BHT and other well interventions became the most used. The share of additional oil produced through the use of EOR and PS has doubled since 2013: 8% in 2013, 16.2% in 2021. Hydraulic fracturing, deep drilling and sidetracking showed the highest efficiency. All this led to the stabilization of the annual oil production in KhMAO – Yugra and even to its growth in 2021.The use of enhanced oil recovery methods on a nonalternative basis in developed fields is especially important, because the share of hard-to-recover reserves is high and reaches 80% for some companies in the Khanty-Mansi Autonomous Okrug – Yugra. For such fields, it is necessary to strengthen scientific research in the field of substantiation of optimal conditions for well construction, as well as the operation of development systems.